In harmony or out of tune: Affective and emotional geographies of all-male choirs in London, UK. (November 2022) - Falconer, Emily
Abstract: This article examines the growing popularity of weekly amateur choral singing for adult men, with a specific focus in London, UK. This paper moves away from discourses of social health and wellbeing to bring together critical studies of masculinity with emotional geographies of sound, to better understand the links between choirs as an affective space and the complex, symbolic relationship between men and their voices. Where research has shown that non-competitive group activity is central to men's sense of connection and provides a space for men to express emotions, friendship and intimacy, there is great potential to analyse how the role of sound (volume, vibrations) and use of choral voice work (softening, blending, harmonies) directly facilitates this connection. This paper remains cautious of presenting group singing as an automatic panacea to disconnection, exploring the exclusions for those who are 'out of tune' and (musically and socially) unable to harmonise with others. Highlights: Affective and emotional geographies of choirs advance critical scholarship into choir singing beyond health and wellbeing. Approaching the study of choir singing through critical social sciences provides opportunities to think about gendered, raced and classed identities, and masculinities especially, as shaped by the circulation of affective bodies in space and time. Research into Critical Studies in Men and Masculinities can benefit from geographies of affect and sound. Further research into affective hostilities and exclusions in choral singing needed.